PRODUCTION OF EXTRACELLULAR ENZYMES BY MESOPHILIC FUNGI OF MUSHROOM COMPOST - AND S. SAXENA, R. D. RAI, B. VIJAY (Indian Phytopathology, 2002)
Ten mesophilic fungi isolated from the compost prepared for cultivation of Agaricus bisporus were assessed for the production of extracellular cellulases, xylanase, -laminarinase, laccase and polyphenol oxidase activities. Most of ·these fungi produced significantly higher activities of extracellular cellulases [filter paper activity (FPA), endoglucanase (CMCase) and ß glucosidase (ß-G)] xylanase and laminarinase but very little or nil activity of laccase and polyphenol oxidase as compared to A. bisporus. A. bisporus did not produce extracellular FPA. Trichoderma viride and Verticillium fungicola showed maximum activities of the cellulases, xylanase and laminarinase. The mesophilic fungi could, therefore, degrade and utilize cellulose hemicellulose and lignin, the important constituents of the mushroom compost.